ECTHR_COMMITTEE 22331/20 vom 13. Mai 2025 , AFFAIRE CIONCA c. ROUMANIE - Ecthr Committee (2025)
Violation de l'article 3 - Interdiction de la torture (Article 3 - Enquête effective) (Volet procédural); Violation: 3